PENERAPAN PENGUATAN POSITIF DALAM MENGEMBANGKAN RASA PERCAYA DIRI ANAK USIA 5-6 TAHUN DI TK NANDA KOTA PALANGKA RAYA - Yuverdina; Rudie; Lukas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the self-confidence of children aged 5-6 years and the implementation of positive reinforcement by teachers in developing self-confidence at Nanda Kindergarten, Palangka Raya City. A qualitative descriptive method was employed. Data were collected through observation, interviews, and documentation. The primary informant was the Class B2 teacher, with supporting informants including the principal, Class A1 teacher, two parents, and two children from Class B2. The findings reveal that children's self-confidence develops diversely. Some children have demonstrated independence in completing tasks, courage to ask questions and express opinions, initiative, confidence to perform in front of the class, positive interaction skills, and a sense of responsibility. Teachers applied positive reinforcement through verbal and non-verbal forms, including gestural, proximity, touch, activity, and token reinforcements. The implementation was based on principles of immediacy, meaningfulness, warmth and enthusiasm, variety, specificity, and avoidance of negative responses. This study implies that consistent application of positive reinforcement through verbal and non-verbal methods based on reinforcement principles can optimally support the development of self-confidence in children aged 5-6 years.